Perbandingan Unit Contoh Lingkaran dan Tree Sampling Dalam Menduga Potensi Tegakan Hutan Tanaman Rakyat Pinus (Studi Kasus Desa Pondok Buluh, Kecamatan Dolok Panribuan, Kabupaten Simalungun) - Okto Prayitno Siahaan; Siti Latifah; Yunus Afifuddin (Program studi Kehutanan USU, 2012)
Information on the potential of forest stands is necessary to know the state and the amount of natural resources contained therein. Potential stands a forest area estimates can be obtained by various methods. This study aims to estimate and compare the potential stands between sample units and determine the most efficient unit instance performed in forest crop production. This study uses systematic random sampling with a sample on circular plots and tree sampling. Circular plots used area of ​​0,05 ha (12,62 m diameter) and tree sampling using 6, 8 and 10 trees in the sample. The results showed the best efficiency levels obtained 6 trees sampling, and accuracy approaching sample of circular plots. Circular plots had the lowest sampling error. Sampling error is less than 5%, so the circular plots had the highest accuracy compared to other sample units. Thus, the circular plots is a sample of the recommended applied to the public plant forest. Keywords: Potential stands, Samples, sampling error, efficiency